Nanotwin formation in Ni–Mo–W alloys deposited by dc magnetron sputtering. (September 2020) - Valentino, Gianna M.; Shetty, Pralav P.; Chauhan, Ankur; Krogstad, Jessica A.; Weihs, Timothy P.; Hemker, Kevin J.
Abstract: Nanotwinned metals and alloys have an attractive suite of properties, but the formation of the underlying nanostructure is generally dependent on the alloy chemistry and processing conditions. This study was undertaken to investigate the effect of deposition rate on nanotwin formation in sputter deposited Ni84 Mo11 W5 that possess ultrahigh strength and stability. Deposition rates of 0.5–2.3 nm/s were examined and the grain size, texture, twin spacing and hardness were characterized. Minimal variations in the underlying nanostructure and attendant hardness were observed, elucidating a wide processing window and the importance of chemistry on the formation of nanotwins in this alloy. Graphical abstract: Image, graphical abstract